2017
DOI: 10.1017/s147895151700058x
|View full text |Cite|
|
Sign up to set email alerts
|

The care experiences of patients who die in residential hospice: A qualitative analysis of the last three months of life from the views of bereaved caregivers

Abstract: Objective: Despite the increasing prominence of residential hospices as a place of death and that, in many regards, this specialized care represents a gold standard, little is known about the care experience in this setting. Using qualitative survey data, we examined the positive and negative perceptions of care in hospices and in other prior settings.Method: Qualitative comments were extracted from the CaregiverVoice survey completed by bereaved caregivers of decedents who had died in 16 residential hospices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…Furthermore, four of the studies represent either perceptions or interventions from Canada that may not have broad applicability to different healthcare systems. 33,[35][36][37][38] However, the themes in the original studies were found to correspond to similar studies from other countries, which also share similarities with the systematic review of international programs included in the synthesis. 28,41,42 For example, a multisetting study in France of the specified elements of palliative care important to patients, caregivers, and providers, found four broad critical dimensions that largely correspond to our essential elements: comprehensive support; management of pain and other symptoms; involvement of families, including clear communication; and the care provided to the imminently dying person, including respecting patient preferences.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Furthermore, four of the studies represent either perceptions or interventions from Canada that may not have broad applicability to different healthcare systems. 33,[35][36][37][38] However, the themes in the original studies were found to correspond to similar studies from other countries, which also share similarities with the systematic review of international programs included in the synthesis. 28,41,42 For example, a multisetting study in France of the specified elements of palliative care important to patients, caregivers, and providers, found four broad critical dimensions that largely correspond to our essential elements: comprehensive support; management of pain and other symptoms; involvement of families, including clear communication; and the care provided to the imminently dying person, including respecting patient preferences.…”
Section: Discussionmentioning
confidence: 59%
“…47 Finally, each of the studies we reviewed has its own inherent limitations, previously described in its respective publication. 28,33,[35][36][37][38]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They show that palliative care in the community gives patients and their families higher quality of life and care. In addition, it is less expensive than the traditional combination of homecare and hospital care as a result of decreasing the number of hospital admissions, shortening the length of hospital stays, and decreasing the frequency of emergency room consultations (Bainbridge et al 2017;Brereton et al 2017;Gomes et al 2013;Seow et al 2019). This article focuses on nurses and their work in specialised palliative homecare in respect of the philosophy of palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…Tidligere studier har også vist at religion kan spille en viktig rolle for mennesker i den palliative fasen (Willig & Wirth, 2018). Den psykososiale omsorgen har vist seg å vaere viktig (Bainbridge, Giruparajah, Zou & Seow, 2017). Omsorgsfulle og støttende omgivelser for pasienten og pårørende er viktig i hjemmebasert palliativ omsorg og betydningsfullt både for samfunnet, for helsepersonell, for pårørende og for pasienten (Akiyama, Hirai, Takebayashi, Morita, Miyashita, Takeuchi, Yamagishi, Kinoshita, Shirahige & Eguchi, 2016).…”
Section: Diskusjonunclassified